ТУРКМАН ВА ҚОРАҚАЛПОҚ АДАБИЁТИДА НАВОИЙ АНЪАНАЛАРИ - Қурамбоев, К. (SCIENCE and SOCIETY, 2021)
The artiete deals with the impact of the work by Alisher Navoiy in Turkmen and Karakalpak classic as well as modern literature, creative peculiarity, stylistic diversity the mastery of poets of fraternal literature are explored comparatively.
Keywords: work; tradition; genre; poem; gazelles; five verses; poetics; image; redif; lyric hero; impact; literary connection